Data Stream Protocols for Real-Time Messaging : Optimizing Performance and Reliability - Shradha Kohli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the design and implementation of data stream protocols for real-time messaging, focusing on key aspects that contribute to their performance and reliability. It examines protocol architectures, data formatting and serialization techniques, error handling mechanisms, and quality of service features. The article compares popular protocols such as WebSocket and MQTT, discusses performance optimization techniques, and addresses security considerations. Emerging trends like WebTransport, HTTP/3, and edge computing integration are also explored, highlighting their potential to reshape the landscape of real-time messaging. By providing a comprehensive overview of current practices and future directions, this article aims to equip developers and system architects with the knowledge needed to design efficient and reliable real-time communication systems.